Intracerebroventricular administration of the (1→6)-β-d-glucan (lasiodiplodan) in male rats prevents d-penicillamine-induced behavioral alterations and lipoperoxidation in the cortex - Carlos Ricardo Maneck Malfatti; Fabio Seidel dos Santos; Jéssica Wouk; Luiz Augusto da Silva; Renan Garcia Michel; André Luiz Snak; Tiago Czervinski; Mário A. Alves da Cunha; Aneli M. Barbosa; Robert F. H. Dekker (Taylor & Francis Group, 2017)
Context: Lasiodiplodan, an exocellular (1→6)-β-d-glucan of molecular weight >1.4 × 106 Da produced by MMPI strain of Lasiodiplodia theobromae (Pat.) Griffon & Maubl. (Brotyosphaeriaceae) is known to exhibit anti-proliferative activity on breast cancer cells (MCF-7), anticoagulant activity when sulfonylated, and reduction in transaminase activity when administered in rats. Objective: The effect of intracerebroventricular (I.C.V) injection of lasiodiplodan on neurotoxicity and behavioural changes induced by d-penicillamine was investigated. Materials and methods: Twenty-four male Wistar rats were initially separated in groups of six and treated with 0.15 μmol/μL of NaCl (Groups Ct and d-Pen) and 0.01 μg/μL of lasiodiplodan (Groups Las and Las + d-Pen). After 15 min, they received 6 μmol/μL of NaCl (Groups Ct and Las) and 2 μmol/μL of d-penicillamine (Groups d-Pen and Las + d-Pen). The animal behavior was observed in an open-field test for 60 min. Twenty-four h later, the animals were sacrificed and histopathological analysis and Thiobarbituric acid reactive substances (TBARS) production measurements were performed. Results: Lasiodiplodan prevented neurotoxicity induced by d-penicillamine significantly reducing the production of TBARS (308%; p < 0.05), and behavioural signs; convulsive and pre-convulsive. No histopathological alterations in the cerebral cortex were observed. Discussion and conclusion: The reduction of TBARS production and convulsive episodes suggests that the protector effect provided by lasiodiplodan passes thought an antioxidant path, possibly interfering in a cascade of neurochemical events, triggering cell death and convulsive episodes. These results demonstrated that lasiodiplodan can be effective in treating neurotoxicity, and reducing damage triggered by convulsions in neuropathies related to GABAergic system.